1997
DOI: 10.1095/biolreprod56.4.891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Insulin and Insulin-Like Growth Factors on Proliferation of Rat Ovarian Theca-Interstitial Cells

Abstract: Hyperplasia of the theca-interstitial (T-I) compartment, such as observed in polycystic ovary syndrome, is associated with ovarian dysfunction. Yet the mechanisms regulating proliferation of T-I cells are virtually unknown. This study was an investigation of the effects of insulin and insulin-like growth factors (IGF-I and IGF-II) on proliferation of rat T-I cells. Purified T-I cells were incubated in chemically defined media. Insulin (1-100 nM) and both IGFs (0.3-30 nM) dose-dependently stimulated DNA synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 29 publications
5
55
0
6
Order By: Relevance
“…One could speculate that, despite similar total IGF-I levels, the IGFBP-1 concentration is decreased in PCOS women, which in turn leads to an increase in the free fraction of IGF-I (24). Moreover, Duleba reported that insulin diminishes not only hepatic IGFBP-1 synthesis but also the intraovarian pool (25). It could promote higher local IGF-I activity.…”
Section: Discussionmentioning
confidence: 98%
“…One could speculate that, despite similar total IGF-I levels, the IGFBP-1 concentration is decreased in PCOS women, which in turn leads to an increase in the free fraction of IGF-I (24). Moreover, Duleba reported that insulin diminishes not only hepatic IGFBP-1 synthesis but also the intraovarian pool (25). It could promote higher local IGF-I activity.…”
Section: Discussionmentioning
confidence: 98%
“…The remaining ovarian tissues were washed thrice with medium 199 containing 25 mmol/l Hepes (pH 7.4), L-glutamine (2 mmol/l), BSA (0.1%), penicillin (100 U/ml) and streptomycin (100 mg/l) to release remaining granulosa cells. To obtain T-I cells, the ovarian tissue was minced actively and repeatedly and incubated for 60 min at 37 8C in the same medium 199, supplemented with collagenase type 1 (5.1 mg/ml) plus 10 mg/ml DNase, as described by Duleba et al (1997).The T-I cells released by this digestion were centrifuged at 250 g for 5 min and washed in collagenase-free medium twice to eliminate remaining collagenase. The dispersed cells were then resuspended in the same McCoy's 5A medium used for the culture of the granulosa cells.…”
Section: Isolation and Culture Of Rat Granulosa Cells And T-i Cellsmentioning
confidence: 99%
“…Finally, insulin acts synergistically with FSH to promote granulosa cell differentiation and proliferation. It also facilitates FSH-dependent steroid production and LH receptor induction in cultured granulosa cells (DULEBA et al, 1997;MAY et al, 1980). This combination of hormones also stimulated follicular development and maintained follicular survival, as well as increased estradiol secretion and promoted oocyte meiosis resumption in goat preantral follicles (CHAVES et al, 2012).…”
Section: Discussionmentioning
confidence: 96%